2017
DOI: 10.1186/s12904-017-0213-0
|View full text |Cite|
|
Sign up to set email alerts
|

Health care use and costs at the end of life: a comparison of elderly Australian decedents with and without a cancer history

Abstract: BackgroundThere is limited population-level research on end-of-life care in Australia that considers health care use and costs across hospital and community sectors. The aim of this study was to quantify health care use and costs in the last 6 months of life in a cohort of elderly Australian decedents and to examine the factors associated with end-of-life resource use and costs.MethodsA retrospective cohort study using routinely collected health data from Australian Government Department of Veterans’ Affairs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
61
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 40 publications
10
61
1
Order By: Relevance
“…Data from the Health Round Table describing ED attendances to the study hospital over the 2017 calendar year showed patients in the last 6 months of life spent an average of 11 h in the ED, and 20 bed days in hospital. 9 Looking more specifically at individual trajectories, a systematic review and meta-analysis of patients with cancer showed that patients with lung cancer were most likely to present to the ED in the last month of life, 10 while Reeve et al 11 reported patients with cancer had a significantly higher rate of healthcare utilisation in the last 6 months of life. Similarly, a retrospective cohort study showed an increase rate of ED presentation in the last 12 months of life for patients with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Health Round Table describing ED attendances to the study hospital over the 2017 calendar year showed patients in the last 6 months of life spent an average of 11 h in the ED, and 20 bed days in hospital. 9 Looking more specifically at individual trajectories, a systematic review and meta-analysis of patients with cancer showed that patients with lung cancer were most likely to present to the ED in the last month of life, 10 while Reeve et al 11 reported patients with cancer had a significantly higher rate of healthcare utilisation in the last 6 months of life. Similarly, a retrospective cohort study showed an increase rate of ED presentation in the last 12 months of life for patients with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…This translates into an annualised cost per QALY in 2018 of $US110,000. A more recent Australian study estimated that the monthly end of life cost of treating cancer patients in 2007 was $11,000 [46]. This translates to an annualised cost per QALY in 2018 of $US120,000.…”
Section: Discussionmentioning
confidence: 99%
“…8e10 Cost analysis of the U.S., Belgium, Canada, England, Germany, The Netherlands, and Norway, shows between 33% and 50% of health-specific purchasing power parityeadjusted hospital expenditure in the last six months of life, is accounted for in the month before death. 11 Previous work has shown a similar scenario among cancer patients in Australia, 12,13 where people are likely to spend time in hospital in the lead up to death and are most likely to die in hospital. 14 This is despite a preference for dying at home 15e19 and for receiving out-of-hospital palliative care.…”
Section: Introductionmentioning
confidence: 93%